Pediatric spinal alignment and spinal development - Léonard Swann Chatelain, MD, MSc; Anne-Laure Simon, MD, PhD; Marc Khalifé, MD, PhD; Emmanuelle Ferrero, MD, PhD (North American Spine Society Journal)
Background: Knowledge of the growth spurt and remaining growth is essential for managing musculoskeletal diseases in children. Accurate prediction of curve progression and timely interventions are crucial, particularly for conditions like adolescent idiopathic scoliosis (AIS). Methods: This study conducted a comprehensive review and synthesis of existing literature on spinal growth, skeletal maturity classifications, and the evolution of sagittal alignment parameters during childhood and adolescence. Key anatomical elements involved in spinal development, natural history of spinal growth, and skeletal maturity assessment systems were analyzed. Results: The analysis highlighted that key parameters such as Pelvic incidence (PI), Pelvic tilt (PT), and Lumbar lordosis (LL) increase significantly with growth, especially during the pubertal growth spurt. In contrast, Sacral slope (SS) remains relatively constant, and Thoracic kyphosis (TK) shows a slight increase. Additionally, there is a posterior shift in the center of gravity as children grow, reflecting progressive postural maturation. The study also reviewed and compared various maturity classification systems, noting the reliability and clinical implications of systems like the Sanders Maturity Stage (SMS) and Tanner-Whitehouse III. Conclusions: Reliable maturity classification systems, such as the Sanders Maturity Stage (SMS) and Tanner-Whitehouse III, allow for tailored treatments to individual growth patterns. Integrating these classification systems into clinical practice enables precise prediction of curve progression and timely therapeutic interventions. This includes options from bracing to surgical techniques like growing rods or vertebral body tethering (VBT), with growth modulation being a key factor in achieving successful outcomes.